Aqueous carbonation of MgSO4 with (NH4)2CO3 for CO2 sequestration. Issue 2 (20th January 2019) - Deng, Chenhui; Liu, Weizao; Chu, Guanrun; Luo, Dongmei; Zhang, Guoquan; Wang, Liming; Yue, Hairong; Liang, Bin; Li, Chun
Abstract: Mineral carbonation is an important technical option for the effective reduction of CO2 emissions. Natural magnesium‐containing minerals, such as serpentine and blast furnace slag (BFS), have recently been used for CO2 storage with an indirect carbonation route using ammonium sulfate. In this study, the effects of the feeding mode and process parameters on the magnesium conversion, product phase, and morphology during the aqueous carbonation of MgSO4 with ammonium carbonate solution were investigated in detail. The results showed that the carbonation ratio with a parallel feed was higher than the forward and reverse feed by about 3–5% with a limited reaction time, and the product size was more uniform. The phase and morphology of the products were affected significantly by the temperature. The highest carbonation ratio appeared at 40°C because only 75% of magnesium was carbonated if hydromagnesite was produced. When the mole ratio of (NH4 )2 CO3 to MgSO4 was 2:1 and the concentration of magnesium sulfate was higher than 0.4 mol·L −1, the carbonated products contain ammonium magnesium carbonate, and the ammonia should be recovered by selective thermal decomposition. When the mole ratio decreased to 1.5:1, only nesquehonite appears with high crystallinity and uniform size. The optimized conditions were therefore selected as 40°C, a mole ratio of 1.5:1, and magnesium sulfate concentration of 0.7 mol·L −1 . Under these conditions the carbonation ratio reached 88%. Additionally, the optimal initial pH of MgSO4 solution was 9.5 (the product was nesquehonite at low pH) while the hydromagnesite will be produced at higher pH (pH more than 10). © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.